Transdentinal cytotoxicity of resin-based luting cements to pulp cells - Garcia, Lucas da Fonseca Roberti [UNESP]; Pontes, Elaine Cristina Voltolini [UNESP]; Basso, Fernanda Gonçalves [UNESP]; Hebling, Josimeri [UNESP]; Costa, Carlos Alberto de Souza [UNESP]; Soares, Diana Gabriela [UNESP] (Springer, 2015)
The aim of this study was to evaluate the transdentinal cytotoxicity of components released from different resin-based luting cements to cultured MDPC-23 odontoblast-like cells and human dental pulp cells (HDPCs). Artificial pulp chamber (APC)/dentin disc sets were distributed into four groups according to the materials tested (n = 10), as follows: G1, control (no treatment); G2, resin-modified glass-ionomer cement (RelyX Luting 2); G3, self-adhesive resin cement (RelyX U200); and G4, conventional resin cement (RelyX ARC). The materials were applied to the occlusal surfaces (facing up) of the dentin discs adapted to the APCs. The pulpal surfaces of the discs were maintained in contact with culture medium. Then, an aliquot of 400 μL from the extract (culture medium + resin-based components that diffused through dentin) of each luting cement was applied for 24 h to HDPCs or MDPC-23 cells previously seeded in wells of 24-well plates. Cell viability analysis was performed by the MTT assay (1-way ANOVA/Tukey test; α = 5 %). For MDPC-23 cells, RelyX ARC (G4) and RelyX Luting 2 (G2) caused greater reduction in cell viability compared with the negative control group (P < 0.05). Only the HDPCs exposed to RelyX ARC (G4) extract showed a tendency toward viability decrease (9.3 %); however, the values were statistically similar to those of the control group (G1) (P > 0.05). In accordance with the safe limits of ISO 10993-5:1999 (E) recommendations, all resin-based luting cements evaluated in this study can be considered as non-toxic to pulp cells. Cytotoxicity of resin-based luting cements is material-dependent, and the different protocols for the application of these dental materials to dentin may interfere with their cytotoxicity.
Keywords: Cytotoxicity; Dentin; Luting cements; Pulp cell